2017
DOI: 10.1155/2017/5931736
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarette Use among Mississippi Adults, 2015

Abstract: Electronic cigarettes (e-cigarettes) are battery-powered devices that deliver nicotine in the form of aerosol. We identify differences and associations in e-cigarette use by sociodemographic characteristics and describe the reported reasons for initiating use among Mississippi adults. We used the 2015 Mississippi Behavioral Risk Factor Surveillance System, which collected information on e-cigarette use from 6,035 respondents. The prevalence of current e-cigarette use and having ever tried an e-cigarette was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…This study examined factors associated with lifetime and current e-cigarette use in the United States, Kentucky, and a large portion of the Central Appalachian region. Our findings were largely consistent with the findings of previous studies 2,9,32 -34 that found age, employment status, and conventional cigarette use were associated with e-cigarette use. Higher rates of e-cigarette use among young adults (aged 18-24) were expected, given research demonstrating that young adults are more susceptible to targeted marketing than older adults.…”
Section: Discussionsupporting
confidence: 92%
“…This study examined factors associated with lifetime and current e-cigarette use in the United States, Kentucky, and a large portion of the Central Appalachian region. Our findings were largely consistent with the findings of previous studies 2,9,32 -34 that found age, employment status, and conventional cigarette use were associated with e-cigarette use. Higher rates of e-cigarette use among young adults (aged 18-24) were expected, given research demonstrating that young adults are more susceptible to targeted marketing than older adults.…”
Section: Discussionsupporting
confidence: 92%
“…Established use of e-cigarettes differed significantly by region, age, race, gender, educational background, annual household income, failure to pay bills in the past 30 days compared to established cigarette, dual users and others who were not established users for both products. Previous research reported that the prevalence of e-cigarettes use in the Mississippi was higher than the average estimate in the US [23,27]. This supports our finding of the highest rates of established e-cigarette, cigarette, and dual use in the South.…”
Section: Discussionsupporting
confidence: 90%
“…However, this area has been under explored for e-cigarettes. For example, previous research focused on adolescents, limited region, nonrepresentative sample for the US or examined ever or past 30 days e-cigarette use which does not measure the establishment of e-cigarette use [20][21][22][23]. Therefore, the objective of this study was to examine the sociodemographic characteristics of established e-cigarette, cigarette, and dual user participants of the Population Assessment of Tobacco and Health (PATH) Study's first wave, which had a representative sample of the US population.…”
Section: Introductionmentioning
confidence: 99%